Review of Dear Ijeawele, or a Feminist Manifesto in Fifteen Suggestions - Sana Goyal (Janeway JS, 2018)
The TED talk speaker and all-round literary superstar Chimamanda Ngozi Adichie follows her 2014 publication, “We Should All Be Feminists”, with another chapbook: Dear Ijeawele, or a Feminist Manifesto in Fifteen Suggestions (2017). An epistolary-style exploration of feminism, it echoes the gender- and sexual-politics of our times, and should be recommended as required reading with immediate effect.
Keywords: archives; Gift Theory; colonialism; India; Museums.